Periprocedural to 1-year safety and efficacy outcomes with the Pipeline Embolization Device with Shield technology for intracranial aneurysms: a prospective, post-market, multi-center study - Rice, Hal (J Neurointerv Surg, 2020)
BACKGROUND: The first and second generations of the Pipeline Embolization Device (PED) have been widely adopted for the treatment of intracranial aneurysms (IAs) due to their high associated occlusion rates and low morbidity and mortality. The objective of this study was to evaluate the safety and effectiveness of the third- generation Pipeline Shield device (PED-Shield) for the treatment of IAs. METHODS: The SHIELD study was a prospective, single-arm, multicenter, post-market, observational study evaluating the PED-Shield device for the treatment of IAs. The primary efficacy endpoint was complete aneurysm occlusion without significant parent artery stenosis or retreatment at 1-year post-procedure and the primary safety endpoint was major stroke in the territory supplied by the treated artery or neurological death. RESULTS: Of 205 subjects who consented across 21 sites, 204 subjects with 204 target aneurysms were ultimately treated (mean age 54.8±12.81 years, 81.4% [166/204] female). Technical success (ie, deployment of the PED-Shield) was achieved in 98.0% (200/204) of subjects with a mean number of 1.1±0.34 devices per subject and a single device used in 86.8% (177/204) of subjects. The primary effectiveness endpoint was met in 71.7% (143/200) of subjects while the primary safety endpoint occurred in six (2.9%) subjects, two (1.0%) of which led to neurological death. CONCLUSIONS: The findings of the SHIELD study support the safety and effectiveness of the PED-Shield for IA treatment, evidenced by high occlusion rates and low rates of neurological complications in the study population. CLINICAL TRIAL REGISTRATION-URL: http://www.clinicaltrials.gov. Unique identifier: NCT02719522.